PENGARUH KOMUNIKASI MASSA DAN MEDIA TERHADAP MAHASISWA FAKULTAS DAKWAH DAN ILMU KOMUNIKASI - Melia Santi; Nasichah Nasichah; Fauziah Puspa Seruni; Ghozi Jaisy Shidiq (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The development of today's era looks more rapidly, the developing era is also accompanied by the development of technology, of course. Life in the modern era, which is full of sophistication, is indeed very helpful in facilitating all kinds of human activities. One of them is the media in communication, communication media can be understood as intermediaries or tools used in mass communication. Mass media can now accelerate its progress, such as television, cellphones, radio, and others. With this progress, the broad scope of human beings throughout the world now feels increasingly narrow because access to interaction is so easy. Not only that, broad information that previously could not be easily accepted by the public, is now able to be received quickly by the wider community. With the accelerated development of this mass media, it is certainly hoped that it will have a positive impact on the wider community in general, especially for students of the Faculty of Da'wah and Communication Studies who do have ties or correlation with the mass media, how can students make the best use of this situation.